ASSESSING THE ROLE OF DEMOGRAPHIC FACTORS ON WORK LIFE BALANCE OF IT PROFESSIONALS IN DELHI-NCR - Kashyap, Eureka; Hoda, Col. Tajmmul (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This research examines the relationship between Demographic Factors and Work-Life Balance among employees in the Information Technology (IT) sector working in the Delhi–NCR region of India. Drawing on primary data and using fundamental statistical methods, the study evaluates the influence of key demographic variables—Age, Gender, and Marital Status—on individuals’ ability to maintain equilibrium between their professional and personal lives. The results highlight a notable association between demographic traits and work-life balance, revealing how these factors interact and shape employees’ experiences. By delving into the challenges IT professionals face in managing dual responsibilities, this study offers meaningful insights. It further serves as a foundation for policy-makers and organizational leaders to develop more supportive frameworks that enhance employee well-being, career stability, and overall workplace satisfaction.